STUDY OF POTENTIAL AND STRATEGIES FOR COLLECTING USED COOKING OIL FROM HOUSEHOLDS AND MICRO ENTERPRISES IN KUTA VILLAGE, BADUNG REGENCY - I Made Alit Widnyana; Azizah Azis; Ayuni Harianti; Suci Rahmawati; Alfian Anhar (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
The study of the potential and strategies for collecting used cooking oil from households and micro-enterprises in Kuta Village, Kuta Subdistrict, Badung Regency, is crucial to support environmental conservation efforts and the development of a sustainable economy. This research aims to identify the potential availability of used cooking oil generated by households and micro-enterprises and optimize efficient and sustainable collection strategies in Kuta Village, Badung Regency. The research method used is descriptive with a quantitative approach and a cross-sectional study design. The research sample includes households and micro-enterprises using cooking oil. The study results show that the average cooking oil consumption for households is 1.05 liters per week, while for micro-enterprises, it is 25.82 liters per week. All respondents (100%) produce used cooking oil, with an average UCO generation of 82.86% of the total cooking oil consumption for households and 8.21% for micro-enterprises. The optimization strategies for UCO collection include direct collection by collectors, utilizing waste banks as collection points, and educating the community about the negative impacts of improper UCO disposal and its processing benefits. These findings provide a basis for efficient, sustainable, and environmentally friendly UCO management.